Insurance Deductions in Patients' Bills: A Case Study on Tamin Ejtemaei Insurance in Iran - Somayeh Khanlari; Ali Janati; Rana Gholamzadeh Nikjoo; Salah Addin Asadi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Insurance deductions are not only caused to failure to achieve the paid costs from the provided services but also are caused to the inefficiency of hospitals. So, this research was conducted to determine the amounts and reasons of insurance deductions in patients’ bills of Tamin Ejtemaei. Methods: This descriptive-practical and retrospective study was conducted in the second season of 2012. The statistical population included records of hospitalized patients (discharged) covered by Tamin Ejtemaei insurance that was conducted as census. The data were collected by using a check list which its validity had been confirmed by experts. The collected information was analyzed through the Excell software and descriptive statistics. Information related to the proposed solution was collected by using group discussion. Results: The amount of applied deductions by Tamin Ejtemaei insurance organization was 47408.62 $ (1$ = 12050 Rials). As bills of hospitalized patients’ records. The mostly applied deductions were respectively related to equipment of surgery-room, the type of  bed during hospital stay, and surgeon fees, however, the main part of these deductions was due to the premium (incompatibility between the price on request and the price of equipment applied for patient) as well as additional request (not consideration of the authorized tariff) by hospital. Conclusion: The hospital efficiency and care therapy quality can be improved by more accurate and better perception of the amount and reasons of insurance deductions and correct management of them.